Information technology. International standardized profiles FVT2nn. Virtual terminal basic class. Register of control object type definitions. FVT215, FVT216. Application RIO record loading control object, terminal, RIO record notification control object Part 3, (15th March 1995) - British Standards Institution,
No abstract available